PHOTOSYNTHETIC AND ANTIOXIDANT ACTIVITY OF OKRA (ABELMOSCHUS ESCULENTUS) SEEDS GERMINATEDON AQUEOUS EXTRACTS OF SELECTED CYANOBACTERIAL SPECIES - PANDEY, ABHISHEK KUMAR; K. ALEX, BLESSYMOLE; P. KOSHY, EAPEN; THOMAS, GEORGE (The Bioscan, 2013)
Okra is a vegetable crop which is having high medicinal properties. The objective of the present investigation was to study the effect of selected cyanobacterial species on growth parameters, photosynthesis and antioxidant system of Okra plant. As compared to control plants, seeds presoaked in the culture extract of Spirulinasp., Chroococcussp. and Anabaena sp. enhanced the germination percentage, vegetative growth, chlorophyll content andantioxidant system (carotenoid content, total phenol content and peroxidase enzyme activity) of Okra (Abelmoschusesculentus). 5% extracts of the selected cyanobacterialspecies showed maximum effect in enhancing growth, biochemical constituents and peroxidase enzyme activity of the plant. Cyanobacterial treatment can be used to increase the photosynthetic and antioxidant activity of other vegetable crops and also as a growth enhancer.